CONVERSATIONAL IMPLICATURE FOUND IN DIALOGUE OF EURO TRIP MOVIE - HUDA, MIFTAHUL (Jurnal Ilmiah Mahasiswa FIB, 2013)
Verbal communication is one of important parts of human‟s life. Onestudy that deals with verbal communication is pragmatics. Pragmatics talksabout people‟s intended meaning, their assumption, their purpose or goals andalso the kind of action. This study attempts to analyze pragmatically theconversational  implied meaning or simply called implicature on the dialogueof Euro Trip movie based on Grice‟s Cooperative Principle and its maxims.The main objective of this study is to discover how utterance can go beyond itsliteral meaning by the disobeying or flouting of some principles by the speakerin dialogue because flouting maxims particularly salient way of getting anaddressee to draw an inference and hence recovers an implicature or impliedmeaning. There are three research problems being observed namely: (1) Whatare the implicatures that occur in dialogue of Euro Trip movie (2) What type ofconversational implicature in the dialogue in the movie entitled Euro Trip (3)What is the function of the implicature. The research design of the study is qualitative approach which employscontent analysis. It is intended to investigate that three research problems inrelation flouting maxim and conversational implicature. The data are theutterances in the dialogue of Euro Trip movie that contain implicature and alsothe data are taken from transcription of Euro Trip movie‟s English subtitles. The result of the study describes the process of identifyingconversational implicature, the type of implicature and the function.Implicature is occured as the result of flouting maxim. The type of implicaturethat occur are generalized and particularized implicature. Implicatures in thisdialogue have four types of particular function named representative, directive,expressive and commissive. The writer expects the next researcher to study theconcept of conversational implicature in different subject like advertisement,TV show, newspaper and many other. The writer also expects the nextresearcher to identify implicature with different theory like theory of relevance. Keywords: Pragmatics, Gricean Maxim, Flouting Maxim Conversationalimplicature,  Euro Trip Movie